EVEKTIVITAS PERMAINAN TRADISIONAL BAREN TERHADAP HASIL BELAJAR LARI SPRINT 100 METER PADA SISWA PUTRA KELAS VIII MTs MA’ARIF SUKANAGARA TAHUN PELAJARAN 2022/2023 - N. Siti Nuraeni Sofa; Mirwan Aji Soleh (JESA-Jurnal Edukasi Sebelas April, 2024)
The results of learning to run short distances are less developed, especially in the 100 meter number. One of the causes, according to the results of direct observation conducted by the author on male students of Class VIII MTs Ma'arif Sukanagara, Darmaraja District, Sumedang Regency, is the situation and conditions of physical education learning itself, it seems that students in general lack varied and challenging learning experiences. Based on the findings in the field and at the same time the solution to this problem, the author wants to try to improve the learning outcomes of short distance running in the form of a game so that students' motivation to learn is maintained. One form of the game that the author will apply is the traditional baren game, "In the implementation of the game, children are required to exert agility and running speed, trying to be able to exceed the opponent's boundary/line of victory more quickly." This game The number of members of each each team of five to 10 children, either all boys, or all girls or a mix of boys and girls Determining the number of team members by suit or lot. Baren traditional games are very close to the impression of fun, various creative expressions, innovative, movement skills, physical fitness will be formed and are very suitable for the needs of junior high school aged children. Besides that, also with the playing atmosphere, the saturation factor can be minimized, the authors can draw the conclusion that the baren game has a significant influence on the learning outcomes of the 100-meter sprint in Class VIII Boys MTs Ma'arif Sukanagara, Darmaraja District, Sumedang Regency.